Isolation of quartz for cosmogenic in situ 14C analysis - Nichols, Keir A.; Goehring, Brent M. (Geochronology, 2019)
Froth flotation is a commonly used procedure for separating feldspars and micas from quartz for the preparation of quartz mineral separates to carry out cosmogenic nuclide analysis. Whilst extracting carbon from quartz we observed in situ carbon-14 (14C) concentrations which were anomalously high and in excess of theoretical geological maximum concentrations. Further etching of sample material reduced carbon yields and 14C concentrations, yet the latter remained unrealistically high. When quartz from the original whole rock sample was isolated in our laboratory, we observed even lower carbon yields and geologically plausible in situ 14C concentrations. After ruling out unlikely geological scenarios and systematic measurement issues, we decided to investigate the quartz isolation procedure as a potential source of 14C contamination. We hypothesised that laurylamine (dodecylamine), an organic compound used as part of the froth flotation procedure, elevates 14C concentrations if residual laurylamine is present. We demonstrate that laurylamine has a 14C modern carbon source and thus has the potential to influence in situ 14C measurements if present in minute but measurable quantities. Furthermore, we show that insufficient sample etching results in contaminant 14C persisting through the step heating of quartz that is subsequently collected with the in situ component released at 1100 ∘C. We demonstrate that froth flotation contaminates in situ 14C measurements. We provide guidelines for the preparation of quartz based on methods developed in our laboratory and demonstrate that all froth-flotation-derived carbon and 14C is removed when applied. We recommend that the procedures presented be used at a minimum when using froth flotation to isolate quartz for in situ 14C measurements.